Factors associated with general practitioners' routines and comfortability with assessing female genital cutting: a cross-sectional survey - Mai Mahgoub Ziyada; R. Elise B Johansen; Mona Berthelsen; Inger-Lise Lien; Bothild Bendiksen (BMC, 2023)
Abstract Background Female genital cutting (FGC) may cause a series of health problems that require specialized healthcare. General practitioners (GPs) are gatekeepers to specialized healthcare services in Norway. To refer girls and women subjected to FGC to appropriate services, GPs need to assess whether the health problems reported by these patients are related to FGC. However, we do not know to what degree GPs assess FGC as a potential cause of the patients' health problems. We also know little about the GPs' patterns of training and knowledge of FGC and their effect on the GPs' assessment of FGC as a potential cause of health problems. Method We employed a cross-sectional online survey among GPs in Norway to examine: 1) patterns of received training on FGC, self-assessed knowledge, and experiences with patients with FGC-related problems and 2) the association between these three factors and the GPs' assessment of FGC as a potential cause of patients' health problems. A total of 222 GPs completed the survey. Data were analysed using binary logistic regression, where we also adjusted for sociodemographic characteristics. Results Two-third of the participants had received training on FGC, but only over half received training on FGC-related health problems. Over 75% of the participants stated a need for more knowledge of FGC typology and Norwegian legislation. While the majority of the participants assessed their knowledge of FGC medical codes as inadequate, this was not the case for knowledge of the cultural aspects of FGC. Female GPs were more likely to have experience with patients with FGC-related health problems than male GPs. Among GPs with experience, 46% linked health problems to FGC in patients unaware of the connection between FGC and such health problems. GPs were more likely to assess FGC as a potential cause of health problems when they had experience with patients having FGC-related problems and when they assessed their knowledge of FGC typology and FGC-related medical codes as adequate. Conclusion To improve their assessment of FGC as a potential cause of patients' health problems, GPs should receive comprehensive training on FGC, with particular emphasis on typology, health problems, and medical codes.